Analysis of The Implementation of Integrated Communication in Employer Branding Management (Case Study at PT Telkom Indonesia (Persero), Tbk) - Ulhaq, Abdullah Wildan; Anggraini, Choiria (UMSU, 2024)
Telkom Indonesia in 2022 received the Best Workplace Asia award from the Great Place to Work Institute and Top 1 Companies Indonesia from LinkedIn. This research aims to find out how the implementation of integrated communication in managing employer branding at PT Telkom Indonesia (Persero), Tbk. This research uses a qualitative approach with a case study method to explore programs, policies, and facilities as an implementation of integrated communication and employer branding aimed at employees as internal stakeholders and prospective employees as external stakeholders. Data collection was conducted through interviews, observations, and documentation studies. Interviews were conducted with Human Capital Communication Employer Branding Telkom Indonesia staff and observation of social media used for employer branding activities. The documentation study was conducted as a complement to explain the employer branding program. The results showed that Telkom Indonesia has four Employee Value Proposition (EVP) used as the foundation in the implementation of employer branding communication, which are learn, grow, contribute, and a great place for digital innovation champions. Forms of integrated communication implementation in managing employer branding at Telkom Indonesia include the FWA (Flexible Working Arrangement) policy, Digistar program, GPDP (Great People Development Program), GPSP (Great People Scholarship Program), AyoBikinNyata, and facilities for employees to realize their startup ideas through the AMOEBA business incubator. Telkom Indonesia has also used various social media and implemented an omnichannel strategy in employer branding communication activities, both internally and externally.